Understanding the role of spacer cation in 2D layered halide perovskites to achieve stable perovskite solar cells. Issue 5 (9th February 2022) - Mahal, Eti; Mandal, Shyama Charan; Pathak, Biswarup
Abstract : Intermolecular H-bonding between organic cations results in the highly rigid geometry of 2D layered halide perovskites leading to reduced octahedral distortion and inorganic layer separation. This improves the optoelectronic property of the materials. Abstract : Intercalation of a large organic cation between metal halide layers provides better energetic stability to the perovskite structure. In this regard large organic cation intercalated two-dimensional layered halide perovskites (2D-LHPs) are receiving research attention due to their improved environmental stability and structural versatility. Here, we present a detailed theoretical investigation on the effect of spacer cations on the structural distortion of the inorganic layer that mainly controls the band edge properties of 2D-LHPs. We have considered pure 2D-LHP systems that include three mono-cation as well as four di-cation spacers. The 2D-LHP systems are A2 PbI4 and APbI4 for mono-cation and di-cation spacers, respectively, where A is the ammonium based organic spacer cation. Moreover, the structural, electronic, and optical properties of the 2D-LHPs have been investigated in detail to determine the origin of the spacer cation influence on the properties of 2D-LHPs. In spite of the mono-cationic nature, the 3-APN spacer cation considered in our study provides exceptionally reduced octahedral distortion (Pb–I–Pb angle ∼177° and 172°) and inorganic layer separation (∼10.17 Å) that results in a reduced band gap and good charge carrier masses. Directional anisotropy observed in the transport as well as optical property will guide the fabrication of high-performance photovoltaic devices. The considered di-cationic systems also possess an impressive band gap, carrier effective mass and optical absorption. Our findings expose the scope of mono-cation based systems as an excellent choice of material for applications in photovoltaics. Therefore, our study finds a design approach for 2D-LHPs to tune their properties through spacer cation engineering for application in photovoltaic devices.